Ari-1 regulates myonuclear organization together with Parkin and is associated with aortic aneurysms - Tan, Kai Li (Dev Cell, 2018)
Nuclei are actively positioned and anchored to the cytoskeleton via the LINC (LInker of Nucleoskeleton and Cytoskeleton) complex. We identified mutations in the Parkin-like E3 ubiquitin ligase Ariadne-1 (Ari-1) that affect the localization and distribution of LINC complex members in Drosophila. ari-1 mutants exhibit nuclear clustering and morphology defects in larval muscles. We show that Ari-1 mono-ubiquitinates the core LINC complex member Koi. Surprisingly, we discovered functional redundancy between Parkin and Ari-1: increasing Parkin expression rescues ari-1 mutant phenotypes and vice versa. We further show that rare variants in the human homolog of ari-1 (ARIH1) are associated with thoracic aortic aneurysms and dissections, conditions resulting from smooth muscle cell (SMC) dysfunction. Human ARIH1 rescues fly ari-1 mutant phenotypes, whereas human variants found in patients fail to do so. In addition, SMCs obtained from patients display aberrant nuclear morphology. Hence, ARIH1 is critical in anchoring myonuclei to the cytoskeleton.